2013
DOI: 10.1007/s12576-013-0262-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in muscle regeneration following eccentric muscle contractions in rat skeletal muscle

Abstract: We examined the role of nitric oxide (NO) in muscle repair and regeneration following repetitive eccentric contractions (ECC). A standardized exercise protocol was used to create eccentric contraction-induced injury to the left tibialis anterior muscle of 48 male Wistar rats (body wt 250-350 g), using a customized isokinetic test device and a bout of 40 ECCs under electrical stimulation. A nitric oxide synthase inhibitor, N(G)-nitro-L-arginine-methyl ester (L-NAME; 35 mg kg(-1) day(-1)), was included in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…It was beyond the scope of this study to examine the role of other mechanisms by which BTJ could attenuate muscle damage, but owing to the seemingly pleotropic nature of phenolic and betalainic compounds and NO, there are a number of possible candidates. For instance, other effects associated with phenolic compounds and NO donors akin to BTJ are anti-inflammatory [25,33] and regenerative, in so far as they appear to have a regulatory role in phagocytosis and promote satellite cell proliferation in skeletal muscle [53,54,55]. Increasing in vivo NO availability has also demonstrated additional biochemical effects that, conceivably, could contribute to improved functional recovery after exercise, such as reduced calpain activity [56], increased muscle blood flow [57,58], and enhanced muscle power potential, possibly via improved Ca 2+ handing [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…It was beyond the scope of this study to examine the role of other mechanisms by which BTJ could attenuate muscle damage, but owing to the seemingly pleotropic nature of phenolic and betalainic compounds and NO, there are a number of possible candidates. For instance, other effects associated with phenolic compounds and NO donors akin to BTJ are anti-inflammatory [25,33] and regenerative, in so far as they appear to have a regulatory role in phagocytosis and promote satellite cell proliferation in skeletal muscle [53,54,55]. Increasing in vivo NO availability has also demonstrated additional biochemical effects that, conceivably, could contribute to improved functional recovery after exercise, such as reduced calpain activity [56], increased muscle blood flow [57,58], and enhanced muscle power potential, possibly via improved Ca 2+ handing [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…), while treatment with the NOS inhibitor l ‐NAME may delay muscle regeneration following acute eccentric exercise (Sakurai et al . ).…”
Section: Reactive Oxygen Species and Exercise Trainingmentioning
confidence: 97%
“…Our previous study, using the same model for ECC as in this study [22], has demonstrated that up to 4 days after ECC, ECC-related reductions in myosin ATPase activity are not accompanied by proteolysis of myosin heavy chain where myosin ATPase is situated. It has been shown that the concentration of nitric oxide increases in the muscle cell for several days after ECC [31] and that increased nitric oxide adversely affects the contractile proper- Muscle damage and resultant depressions in muscle performance are universal symptoms familiar to most athletes, because muscle contractions during many of sport activities and training include a substantial eccentric component.…”
Section: Discussionmentioning
confidence: 99%